2016
DOI: 10.1186/s12891-016-1332-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk of infection in primary, elective total hip arthroplasty with direct anterior approach or lateral transgluteal approach: a prospective cohort study of 1104 hips

Abstract: BackgroundThe direct anterior approach (DAA) is increasingly popular for hip replacement. However, the small incision and the location near to the groin might increase the risk of periprosthetic joint infection (PJI). We asked the questions (i) whether there is an increased risk of infection for this approach, and (ii) whether the spectrum of microorganisms differs between patients with DAA and those with lateral transgluteal approach (LAT).MethodsAll patients operated between 08/2006 and 12/2013 were followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 27 publications
2
21
3
1
Order By: Relevance
“…This rate of PJI is consistent with two systematic reviews which have reported an average risk of PJI after hip arthroplasty for the treatment of a hip fracture between 2-4% [10], [11]. This is a higher rate of PJI than the 0.5-2% PJI rate typically found in the primary elective hip arthroplasty population [24], [25]. It is unsurprising that hip fracture patients have higher rates of PJI than the elective hip arthroplasty population given the increased age, poor nutritional status, and large number of comorbidities of hip fracture patients [26].…”
Section: Plos Onesupporting
confidence: 90%
“…This rate of PJI is consistent with two systematic reviews which have reported an average risk of PJI after hip arthroplasty for the treatment of a hip fracture between 2-4% [10], [11]. This is a higher rate of PJI than the 0.5-2% PJI rate typically found in the primary elective hip arthroplasty population [24], [25]. It is unsurprising that hip fracture patients have higher rates of PJI than the elective hip arthroplasty population given the increased age, poor nutritional status, and large number of comorbidities of hip fracture patients [26].…”
Section: Plos Onesupporting
confidence: 90%
“…We cannot make a statement about the risk for C. avidum PJI in colonized patients since we only have a follow-up of 6 to 12 months after primary hip arthroplasty in 21 colonized patients. In general, the anterior approach is not seen as a risk factor for infections [29]. However, obesity, defined as an elevated BMI, is a known general risk factor for PJIs [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…One of the limitations is related to the complications that might occur later in time, although a recent Bayesian metaanalysis study [25] that analysed 38 studies (6485 patients) reported that most complications relative to the approach occur in the early post-operative settings. Moreover, a prospective cohort study of 1104 hip arthroplasties carried out by Ilchmann et al [27] comparing the short and long term risks of infection between the two approaches also reported no increased risk for the DAA. Therefore, we consider our follow-up period to be sufficient to detect approach-related complications.…”
Section: Discussionmentioning
confidence: 91%
“…By the current study we had no intention to compare either the short term or long term clinical outcomes by means of hip and quality of life scores, as this has been widely dissected by previous studies, with a virtually unanimous conclusion of no long term difference, regardless of objectified muscle spearing findings [6,7,15,27].…”
Section: Discussionmentioning
confidence: 97%